High pregnancy rates in humpback whales (Megaptera novaeangliae) around the Western Antarctic Peninsula, evidence of a rapidly growing population. Issue 5 (2nd May 2018) - Pallin, Logan J.; Baker, C. Scott; Steel, Debbie; Kellar, Nicholas M.; Robbins, Jooke; Johnston, David W.; Nowacek, Doug P.; Read, Andrew J.; Friedlaender, Ari S.
Abstract : Antarctic humpback whales are recovering from near extirpation from commercial whaling. To understand the dynamics of this recovery and establish a baseline to monitor impacts of a rapidly changing environment, we investigated sex ratios and pregnancy rates of females within the Western Antarctic Peninsula (WAP) feeding population. DNA profiling of 577 tissue samples (2010–2016) identified 239 males and 268 females. Blubber progesterone levels indicated 63.5% of the females biopsied were pregnant. This proportion varied significantly across years, from 36% in 2010 to 86% in 2014. A comparison of samples collected in summer versus fall showed significant increases in the proportion of females present (50% to 59%) and pregnant (59% to 72%), consistent with demographic variation in migratory timing. We also found evidence of annual reproduction among females; 54.5% of females accompanied by a calf were pregnant. These high pregnancy rates are consistent with a population recovering from past exploitation, but appear inconsistent with recent estimates of WAP humpback population growth. Thus, our results will help to better understand population growth potential and set a current baseline from which to determine the impact of climate change and variability on fecundity and reproductive rates.